Exploring the Causes and Effects of Infection on Human Health - Hussain Abdullah Yousef Al Makrami,; Abdullah Awadh Hassan Alsulaymi,; Abdullah Ali Mohammed Alsaiaari,; Saud Awad Alanazi,; Ibrahim Amer Ahmed Albariqi,; Sami Amer Ahmed Albariqi,; Naif Eid Al Oufi,; Saad Mohammed Zaher Alalyani,; Amer Ali Amer Alshehry, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Efforts made to comprehend the essence of disease and its causes have shaped the history of medicine. Yet, unless one invokes some kind of supernatural causes, it is often impossible to answer the question of why a particular individual suffers from this or that malady. Nevertheless, one interesting exception to this rather unsatisfactory situation was always seen in the instance of infectious diseases. Here it is possible to discern a relatively simple cause and effect chain, which in turn offers the practionable perspectives of their successful prophylaxis and cure. The discovery that anthrax was caused by a bacillus was an important turning point in medical history. Previous to this seminal event, so called ‘black death’ and other plagues were considered as the manifestation of God’s curse. Appropriate preventive and therapeutic measures were hence seen in terms of piety and futile penance rather than crude pathogenetic mechanisms. Since the mid 19th Century, and in no small part due to advances from bacterial theory and histological techniques, experimental infections were subjected to rational and systematic scrutiny. Soon, the battle against long dreaded scourges like smallpox, cholera and plague appeared to have been won. There was hence an almost universal belief, that in the foreseeable future microbes would be tamed, and that the age of infectious diseases was almost past